(untitled) (Bangladesh Journal of Botany, 2021)
Effects of perlite, vermiculite, and grass charcoal on root growth of Isatis and soil nutrients migration were studied, and the plant growth indicators and some soil properties of upper (0 5cm) and lower layer (5 15cm) were analyzed. The experiment treatments were loess (CK), loess : perlite = 3 : 1(A), loess : grass charcoal = 3 : 1(B), loess : vermiculite = 3 : 1(C), loess: perlite: grass charcoal = 6 : 1 : 1(A1), loess: perlite: vermiculite = 6 : 1 : 1(B1), loess: grass charcoal: vermiculite = 6 : 1 : 1(C1). The results showed that soil pH of vermiculite-containing treatments in the upper layer and grass charcoal treatment in the lower layer decreased significantly. Before planting, the available potassium and phosphorus of the upper layer were significantly higher than those of the lower layer, and soil organic matter (SOM) was slightly higher than that of the lower layer. After planting, the decrease of available potassium in the upper layer was less than that of the lower layer, and the decrease of available phosphorus and increase of SOM in the upper layer were slightly higher than that of the lower layer. In sum, it is preferred to choose B (loess : grass charcoal = 3 : 1) and A1 (loess: perlite: grass charcoal = 6 : 1 : 1) to improve the soil nutrient and utilization efficiency. Bangladesh J. Bot. 50(3): 947-954, 2021 (September) Special